AUTOMATIC IDENTIFICATION OF THE GEOMORPHOLOGIC AND MORPHOTECTONIC FEATURES OF THE SOUTH CRETAN MARGIN, USING OBJECT BASED IMAGE ANALYSIS - Kouli, R.; Argialas, D.; Nomikou, P.; Lykousis, V. (Bulletin of the Geological Society of Greece, 2016)
This paper is focused on the study of the South Cretan Margin, from a Digital Seabed Elevation Model, by employing Object Based Image Analysis. The goal is the automatic extraction of geomorphological and morphotectonic features based on morphological criteria and topological relations. A Digital Seabed Elevation Model of 150x150 meters resolution was employed. At first, slope, curvature, planform curvature, profile curvature and Topographic Position Index were derived from this DSEM. Five different layers of segmentation were created in order to extract the final geomorphological classes, Ptolemy trough, intraslope basins, main basins, small basins, continental shelf, plains, continental slope, escarpments, canyons, spurs, discontinuities, fault like and fault surface. The results were evaluated quantitatively, through the established indices Completeness, Correctness and Overall Quality. For computing these indices, it was necessary to digitize the boundaries of the objects derived by photo-interpretation. Then, the computation of the above indices, took place by comparing the results of digitized photo-interpretation boundaries, to the extracted feature boundaries through OBIA analysis (in shapefile). It is worth noting that, the results of the evaluation are quite satisfactory. Thus, the developed OBIA method is considered successful.